Inner Dialogical Communication and Pathological Personality Traits - Łysiak, Małgorzata (Frontiers in Psychology, 2019)
Dialogicality and its relation to personality traits have been extensively explored since the evolution of dialogical self theory. However, the latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) proposes a new hybrid personality disorder system and, thereby, a new model of pathological personality traits. As of now, there are no studies which show the relationships between self-talk, internal dialogicality, and pathological traits. Thus, the aim of this study was twofold: (a) to investigate the relationship between self-talk and pathological personality traits and (b) to explore the possible affinity between pathological structure of personality and dialogicality. A representative sample of 458 individuals from the nonclinical population, aged 18–67 (M=30.99, SD=10.27), including 52% women, completed three questionnaires: the Self-Talk Scale by Brinthaupt, Hein, and Kramer, the Internal Dialogical Activity Scale by Oleś, and the Personality Inventory for DSM-5 by Krueger, Derringer, Markon, Watson, and Skodol. To verify the correspondence between self-talk, internal dialogues, and pathological personality traits, the Pearson product–moment correlation coefficients (Pearson’s r) and canonical correlation analysis were used. The results supported the hypotheses about the specific relationship between internal dialogical activity and five crucial dysfunctional personality traits related to the hybrid DSM-5 system of diagnosis. People characterized as having emotional lability, anxiousness, and separation insecurity (high negative affectivity), with unusual beliefs and experiences, as well as eccentricity (high psychoticism), are prone to having ruminative and confronting dialogues. The correlation between pathological personality traits and self-talk were statistically significant, but the relationships are very small.